JMP 13 basic analysis (SAS Institute, 2016)
JMP 13 Basic Analysis covers the initial types of analyses that you often perform in JMP, such as univariate, bivariate, and oneway analyses. Creating tables of summary statistics with the Tabulate platform is included along with approximating sampling distributions using bootstrapping. Find information about how to clean up your data before performing analyses. Read about performing powerful parametric and nonparametric simulation capability using Simulation.
Includes bibliographical references and index. - Online resource; title from title page (viewed September 22, 2016)
Keywords: JMP (Computer file); Mathematical analysis; Statistics -- Graphic methods; Mathematical statistics -- Data processing; Information visualization; Analyse mathématique; Statistique; Méthodes graphiques; Statistique mathématique; Informatique; Visualisation de l'information; MATHEMATICS; Applied; MATHEMATICS; Probability & Statistics; General; Mathematical statistics; Data processing; Statistics; Graphic methods